Recent Advances in PVP Bolted Joint Technology. (2015) - Brown, W.
Abstract: This paper outlines several areas of advancement in pressure vessel and piping bolted joints that have been researched in recent years. The topics include: The creation of a quantitative risk assessment for determining the likelihood of joint leakage, which allows the assessment of the most at-risk joints in any given plant or project. This enables resources and urgency to be assigned appropriately to only those joints that require it. Further examination of the creep/relaxation characteristics of bolt materials will be presented. This information is based on recent laboratory testing performed on a range of bolt materials and will eventually enable the prediction of the influence of metallic component relaxation on joint integrity. Assembler Qualification will also be examined, based on the system of training and demonstration that has been developed for the IES "Train-the-Trainer" program that fully complies with ASME PCC-1 Appendix A.